Lumpy Skin Disease Spread in India: A Review - Amey.V.Mahadik; Prathmesh.G.Nagargoje; Amol.S.Jadhav; Bandu.S.Pawar (The Bioscan, 2025)
The transboundary illness lumpy skin disease, which is significant commercially, affects cows and buffaloes. The lumpy skin disease virus (LSDV), a constituent of the Poxviridae family and genus Capripoxviridae, causes it to manifest (Neethling strain). The virus has been compared to Allerton and Bovine Mammilitis Virus, which results in lesions that resemble those found in the early stages of LSD. Some of the key clinical signs are typical skin nodules on the body, increased body heat, nasal discharge, excessive salivation, breast tissue inflammation, lessened milk supply, cachexia, depression, and unwillingness to move. The contagion is widespread in African countries and the Middle East regions. Asia and other areas have recently started to experience expansion. LSD morbidity rates of 13.93 percent in cattle have recently been observed in India (2022) during six months. The economic impact of this viral disease is quite concerning due to the severe morbidity and high mortality rates it produces in unprotected cattle and calves. It could also be used as a tool in economic bioterrorism and threaten international trade. The COVID-19 outbreak and the subsequent implementation of sanctions have hastened the disease's spread in India. The current study aims to provide recent developments on a range of disease-related topics, including transmission, epidemiology, diagnosis, and preventative and therapeutic approaches. This review's findings emphasize the significance of LSDV diagnostics using molecule and strain monitoring. The information would also aid in developing discriminative and prevention strategies for LSDV in India.